Phenomenological Review of the Role of the Internal Control System and Corporate Culture in Enterprise Resource Planning (ERP) System Implementation to Produce Quality Financial Reports - Lawita, Florencia Irena; Santoso, Yosef Budi; Utomo, Prio (Universitas Batanghari Jambi, 2024)
The best way to influence the quality of financial reports is to use an Enterprise Resource Planning (ERP) system. Implementation of an ERP system with an internal control system and corporate culture can help companies and management make decisions. This study aims to look at the interpretative-phenomenological role of internal control systems and corporate culture by implementing ERP systems to produce quality financial reports. The research method uses a qualitative interpretative-phenomenological paradigm. The informant determination technique in this study used purposive sampling. The data collection procedure used in this study was designing research instruments for the interview process, making transcripts, then conducting interviews with nine informants. The results of this study, there is an internal control system and corporate culture, with the implementation of the ERP-SAP system carried out in accordance with established Standard Operating Procedures, resulting in quality financial reports.